Effect of using complete feed containing protected soybean groat on production performance and feed efficiency of fattening Thin-Tailed Sheep - Riyanto, Joko; Pramono, Ahmad; Kurniawati, Dhyan Ayu; Mahmudah, Fitrotul; Nissa, Nasta 'Ainun (Jurnal Ilmu Peternakan Terapan, 2024)
This study aimed to determine the effect of using complete feed containing protected soybean groats on the production performance and feed efficiency of fattening thin-tailed sheep. Protection using 37% formaldehyde as much as 1% of dry soybean groats to bypass protein during rumen fermentation. A total of 15 male thin-tailed sheep, aged 12 months with an initial body weight of 23.43±1.40 kg were divided into 3 groups of feed treatments, namely the first group (P1) complete feed 100%, (P2) complete feed 90% + protected soybean groats 10%, and (P3) complete feed 80% + protected soybean groats 20%. Protection of soybean groats using 37% formaldehyde was given as 1% dry matter. The research design used a Completely Randomized Design (CRD). Data were analyzed using analysis of variance, and differences between treatments were further tested with Duncan's Multiple Range Test. The results showed a significantly different effect (P<0.001) on dry matter consumption but not significantly different (P>0.05) on daily body weight gain, relative daily body weight gain, feed conversion, and feed efficiency. The conclusion of the research was that the use of complete feed containing 20% protected soybean groats was efficient due to its ablity to increase dry matter consumption and the FCG produced was low so that higher IOFC was obtained.